Training workshop on use of tools and statistics to support decision making in agricultural sector - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Workshop held in Tegucigalpa, July 13 to 17, 2015 with the participation of officers from the Secretary of Agriculture and Livestock, Copeco, among others. Photos: D. Obando (CIAT)